Comes the dark - Prescott, Michael (New York : Signet, 1999)
As children, Erica and her brother, Robert, were the only survivors at the scene of a crime. As adults, Erica is a strong woman who has managed to build a new life, but Robert retreated to a remote cabin in the woods. And when a local girl is gruesomely murdered, Robert is the first person police suspect.
Keywords: Murder -- Fiction; Suspense fiction